Antioxidant, anti-inflammatory, anti-apoptotic, and skin regenerative properties of an Aloe vera-based extract of Nerium oleander leaves (NAE-8®) - Benson KF; Newman RA; Jensen GS (Dove Medical Press, 2015)
Kathleen F Benson,1 Robert A Newman,2,3 Gitte S Jensen1 1NIS Labs, Klamath Falls, Oregon, USA; 2University of Texas MD Anderson Cancer Center, Houston, TX, USA; 3Nerium Biotechnology, Inc, San Antonio, TX, USA Objective: The goal for this study was to evaluate the effects of an Aloe vera-based Nerium oleander extract (NAE-8®), compared to an extract of A. vera gel alone (ALOE), and to an aqueous extract of N. oleander (AQ-NOE) in bioassays pertaining to dermatologic potential with respect to antioxidant protection, anti-inflammatory effects, and cytokine profiles in vitro. Methods: Cellular antioxidant protection was evaluated in three separate bioassays: The cellular antioxidant protection of erythrocytes (CAP-e) assay, protection of cellular viability and prevention of apoptosis, and protection of intracellular reduced glutathione levels, where the last two assays were performed using human primary dermal fibroblasts. Reduction of intracellular formation of reactive oxygen species (ROS) was tested using polymorphonuclear cells in the absence and presence of oxidative stress. Changes to cytokine and chemokine profiles when whole blood cells and human primary dermal fibroblasts were exposed to test products were determined using a 40-plex Luminex array as a method for exploring the potential cross-talk between circulating and skin-resident cells. Results: The NAE-8® provided significantly better antioxidant protection in the CAP-e bioassay than AQ-NOE. NAE-8® and AQ-NOE both protected cellular viability and intracellular reduced glutathione, and reduced the ROS formation significantly when compared to control cells, both under inflamed and neutral culture conditions. ALOE showed minimal effect in these bioassays. In contrast to the NAE-8®, the AQ-NOE showed induction of inflammation in the whole blood cultures, as evidenced by the high induction of CD69 expression and secretion of a number of inflammatory cytokines. The treatment of dermal fibroblasts with NAE-8® resulted in selective secretion of cytokines involved in collagen and hyaluronan production as well as re-epithelialization during wound healing. Conclusion: NAE-8®, a novel component of a commercial cosmetic product, showed beneficial antioxidant protection in several cellular models, without the induction of leukocyte activation and secretion of inflammatory cytokines. The biological efficacy of NAE-8® was unique from both ALOE and AQ-NOE. Keywords: CAP-e bioassay, dermal fibroblasts, oxidative damage, ROS formation, safety